2019
DOI: 10.1051/0004-6361/201935918
|View full text |Cite
|
Sign up to set email alerts
|

Photospheric magnetic structure of coronal holes

Abstract: In this study, we investigate in detail the photospheric magnetic structure of 98 coronal holes using line-of-sight magnetograms of SDO/HMI, and for a subset of 42 coronal holes using HINODE/SOT G-band filtergrams. We divided the magnetic field maps into magnetic elements and quiet coronal hole regions by applying a threshold at ±25 G. We find that the number of magnetic bright points in magnetic elements is well correlated with the area of the magnetic elements (cc=0.83 ± 0.01). Further, the magnetic flux of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…The strength of the photospheric magnetic field underlying the CHs is distributed around 2.9 ± 1.9 G which is in agreement with most results found in the literature and shows that CHs are mostly covered by low magnetic field. v) We confirm previous studies (Hofmeister et al, 2017;Heinemann et al, 2018b;Hofmeister et al, 2019) that the magnetic configuration of CHs is highly dependent on the abundance and field strength of the small unipolar magnetic elements (flux tubes), which only cover a small fraction of the CH area.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The strength of the photospheric magnetic field underlying the CHs is distributed around 2.9 ± 1.9 G which is in agreement with most results found in the literature and shows that CHs are mostly covered by low magnetic field. v) We confirm previous studies (Hofmeister et al, 2017;Heinemann et al, 2018b;Hofmeister et al, 2019) that the magnetic configuration of CHs is highly dependent on the abundance and field strength of the small unipolar magnetic elements (flux tubes), which only cover a small fraction of the CH area.…”
Section: Discussionsupporting
confidence: 90%
“…When interpreting such parameters a relative comparison should be preferred rather than relying on absolute values. Hofmeister et al (2019) showed that the photospheric magnetic field underlying CHs can be divided into 3 categories: ≈ 22 ± 4% of the signed magnetic flux is contributed by a slightly unbalanced background field. ≈ 5.0 ± 0.1% come from small scale unipolar magnetic elements (flux tubes, FTs) nearly symmetrically distributed over both polarities and which are associated with the super-, meso-, and granular motion of the photosphere.…”
Section: Analysis Of the Underlying Photospheric Magnetic Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…The total area covered by long-lived magnetic elements with lifetimes > 4 days is strongly correlated with the unbalanced magnetic flux of CHs (cc = 0.99). These magnetic elements account for ≈ 68% of the unbalanced "open" magnetic flux of CHs at typical coverages of about 3% of the total CH area (Hofmeister et al, 2019;Heinemann et al, 2019). Heinemann et al (2018a,b) investigated a long-lived low-latitude CH observed by the Solar Dynamics Observatory (SDO) and Solar Terrestrial Relations Observatory (STEREO) spacecraft over ten solar rotations from February 2012 to October 2012 (see Figure 7).…”
Section: Introductionmentioning
confidence: 99%